A manufacturing renaissance? Industrialization trends in the developing world - Hagen Kruse; Emmanuel Mensah; Kunal Sen; Gaaitzen de Vries (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper examines industrialization trends in developing countries. It uses the GGDC/UNU-WIDER Economic Transformation Database, which provides time series of employment and real and nominal value added annually by 12 sectors in 51 countries for the period 1990-2018. Until the early 2000s de-industrialization was widespread, but then the trend reversed. Regressions that control for income and demographic trends suggest significant employment industrialization in developing Asia and sub-Saharan Africa. We explore the nature of this manufacturing renaissance.
Keywords: N10; O14; 330; industrialization; Economic Transformation Database; manufacturing renaissance